Dynamic expressions of hypothalamic genes regulate seasonal breeding in a natural rodent population. Issue 15 (5th August 2019) - Wang, Dawei; Li, Ning; Tian, Lin; Ren, Fei; Li, Zhengguang; Chen, Yan; Liu, Lan; Hu, Xiangfa; Zhang, Xuechang; Song, Ying; Hut, Roelof A.; Liu, Xiao‐Hui
Abstract: Seasonal breeding is a universal reproductive strategy in many animals. Hypothalamic genes, especially type 2 and 3 iodothyronine deiodinases ( Dio2 / 3 ), RFamide‐related peptide 3 ( Rfrp‐3 ), kisspeptin ( Kiss‐1 ) and gonadotropin‐releasing hormone ( GnRH ), are involved in a photoperiodic pathway that encodes seasonal signals from day length in many vertebrate species. However, the seasonal expression patterns of these genes in wild mammals are less studied. Here, we present a four‐year field investigation to reveal seasonal rhythm and age‐dependent reproductive activity in male Brandt's voles ( Lasiopodomys brandtii ) and to detect relationships among seasonal expression profiles of hypothalamic genes, testicular activity, age and annual day length. From breeding season (April) to nonbreeding season (October), adult male voles displayed a synchronous peak in gonadal activity with annual day length around summer solstice, which was jointly caused by age structure shifts and age‐dependent gonadal development patterns. Overwintered males maintained reproductive activity until late in the breeding season, whereas most newborn males terminated gonadal development completely, except for a minority of males born early in spring. Consistently, the synchronous and opposite expression profiles of Dio2/3 suggest their central function to decode photoperiodic signals and to predict the onset of the nonbreeding season. Moreover, changes in Dio2/3 signals may guide the actions of Kiss‐1 and Rfrp‐3 to regulate the age‐dependent divergence of reproductive strategy in wild Brandt's vole. Our results provide evidence on how hypothalamic photoperiod genes regulate seasonal breeding in a natural rodent population.